α-Actinin 4 Links Vasopressin Short-Term and Long-Term Regulation of Aquaporin-2 in Kidney Collecting Duct Cells - Ho, Cheng-Hsuan; Yang, Hsiu-Hui; Su, Shih-Han; Yeh, Ai-Hsin; Yu, Ming-Jiun (Frontiers in Physiology, 2021)
Water permeability of the kidney collecting ducts is regulated by the peptide hormone vasopressin. Between minutes and hours (short-term), vasopressin induces trafficking of the water channel protein aquaporin-2 to the apical plasma membrane of the collecting duct principal cells to increase water permeability. Between hours and days (long-term), vasopressin induces aquaporin-2 gene expression. Here, we investigated the mechanisms that bridge the short-term and long-term vasopressin-mediated aquaporin-2 regulation by alpha-actinin 4, an F-actin crosslinking protein and a transcription co-activator of the glucocorticoid receptor. Vasopressin induced F-actin depolymerization and alpha-actinin 4 nuclear translocation in the mpkCCD collecting duct cell model. Co-immunoprecipitation followed by immunoblotting showed increased interaction between alpha-actinin 4 and glucocorticoid receptor in response to vasopressin. ChIP-PCR showed results consistent with alpha-actinin 4 and glucocorticoid receptor binding to the aquaporin-2 promoter. Alpha-actinin 4 knockdown reduced vasopressin-induced increases in aquaporin-2 mRNA and protein expression. Alpha-actinin 4 knockdown did not affect vasopressin-induced glucocorticoid receptor nuclear translocation, suggesting independent mechanisms of vasopressin-induced nuclear translocation of alpha-actinin 4 and glucocorticoid receptor. Glucocorticoid receptor knockdown profoundly reduced vasopressin-induced increases in aquaporin-2 mRNA and protein expression. In the absence of glucocorticoid analog dexamethasone, vasopressin-induced increases in glucocorticoid receptor nuclear translocation and aquaporin-2 mRNA were greatly reduced. Alpha-actinin 4 knockdown further reduced vasopressin-induced increase in aquaporin-2 mRNA in the absence of dexamethasone. We conclude that glucocorticoid receptor plays a major role in vasopressin-induced aquaporin-2 gene expression that can be enhanced by alpha-actinin 4. In the absence of vasopressin, alpha-actinin 4 crosslinks F-actin underneath the apical plasma membrane, impeding aquaporin-2 membrane insertion. Vasopressin-induced F-actin depolymerization in one hand facilitates aquaporin-2 apical membrane insertion and in the other hand frees alpha-actinin 4 to enter the nucleus where it binds glucocorticoid receptor to enhance aquaporin-2 gene expression.